PENERAPAN INOVASI KERTAS MENAMPIK (KARANGGETAS MENCEGAH KANKER SERVIKS) DI DESA KARANGGETAS KECAMATAN BANGODUA - Indra Ruswadi; Priyanto, Priyanto; Nengsih Yulianingsih (Pusat Riset dan Inovasi Nasional, 2022)
Background: As is known, cervical cancer is a cancer with the 2nd highest incidence rate in Indonesia after breast cancer. With the high cases of cervical cancer in the community, the question arises, how much is the understanding of Village Empowerment and Family Welfare (PKK) cadres in efforts to prevent cervical cancer in their area, especially teenagers about cervical cancer. Objective: To find out how the efforts of PKK cadres, especially Pokja IV TP PKK Desa in providing KIE (Communication, Information and Education) to the people of Karanggetas Village, Bangodua District in preventing cervical cancer by implementing the Kertas Menampik innovation (Karanggetas Preventing Cervical Cancer). PKM (Community Service) is held at the Kuwu Office, Karanggetas Village, Bangodua District, Indramayu Regency from April 18-23 2022 every 10.00 WIB - 14.00 WIB for 6 (six) days. The participants came from the Pokja IV TP PKK Village management and the Posyandu Cadre of Karanggetas Village, Bangodua District, Indramayu Regency as many as 34 people. The materials needed in the meeting with Pokja IV TP PKK cadres, Karanggetas Village, Bangodua Subdistrict, namely: posters, leaflets and a description sheet of the Kertas Menampik innovation. This material was donated to TP PKK Desa, especially Pokja IV TP PKK Desa Karanggetas Subdistrict so that PKK cadres can use it in providing KIE (Communication, Information and Education) about cervical cancer prevention. The results of the activity: PKK cadres are very happy and welcome this innovation and will disseminate information about cervical cancer prevention to the people of Karanggetas Village, Bangodua District. Conclusion: the kertas menampik innovation has been applied to the next PKK cadres, the PKK cadres are planning to socialize this effort to the community, both during posyandu and outside posyandu activities. Suggestion: The implementation of this innovation should involve all components including: academia, business, community, government and media.